(untitled) (American Journal of Islam and Society, 2022)
This book examines Sufism in Ottoman Egypt in the seventeenth and eighteenth centuries. Contrary to the traditional historiography that interpreted these two centuries as a period of stagnation and/or decline for Sufism and Sufi scholars, Rachida Chih argues that these centuries were fruitful, productive, and dynamic for Sufism in Ottoman Egypt. Chih builds her narrative around the mobilization and interaction of ideas, people, and institutions, focusing her thesis on the Khalwatiyya Sufi order.